PENGEMBANGAN KEMASAN SEBAGAI UPAYA PENINGKATAN POTENSI PEMASARAN CRÈME ROYALE - Tunjungsari, Hetty Karunia; Yukianti, Chiara Rizka; Buana, Salsabilla Ayundha Martsha (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
The number of Micro, Small and Medium Enterprises (MSMEs) in Indonesia reaches 64.2 million, contributing more than 60% to Gross Domestic Income (GDP) and playing a key role in Indonesia's economic growth. The Covid-19 pandemic has encouraged a change in consumer shopping patterns from offline to online, opening up opportunities and challenges for MSMEs, especially in the food and beverage sector. Ice cream products have great potential in Indonesia driven by the lifestyle of the millennial generation who love snacks, especially ice cream, providing opportunities for MSMEs in the food and beverage sector. Packaging is considered important to add value to products, attract consumers' attention, and increase marketing potential. Through packaging development training and focus group discussions, the Universitas Tarumanagara community engagement team aims to improve the ability of Crème Royale MSMEs, in developing packaging that can have a positive impact on the marketing of ice cream products. These activities include training in the use of design making applications, material selection, and social media management for online marketing. Crème Royale has used the Whatsapp and Instagram platforms for bookings and promotions. The development of packaging is expected to help Crème Royale market its products more effectively, increase sales, and contribute to economic growth. The resulting activities are packaging design development, comprehensive knowledge of packaging design, and focus group discussion to develop packaging that can be implemented by Crème Royale. The community engagement team registered Intellectual Property Rights for the design of Crème Royale ice cream packaging. This activity was carried out for Crème Royale partners with the aim of providing assistance in developing packaging, increasing marketing potential, and preparing the basis for a follow-up activity plan after the implementation of community engagement activities. ABSTRAK Jumlah Usaha Mikro, Kecil, dan Menengah (UMKM) di Indonesia mencapai 64,2 juta, menyumbang lebih dari 60% terhadap Pendapatan Domestik Bruto (PDB) dan memegang peran kunci dalam pertumbuhan ekonomi Indonesia. Adanya pandemi Covid-19 mendorong perubahan pola belanja konsumen dari offline menjadi online sehingga membuka peluang dan tantangan bagi UMKM, terutama di sektor makanan dan minuman. Produk es krim memiliki potensi besar di Indonesia didorong oleh gaya hidup generasi milenial yang menyukai makanan ringan, terutama es krim, memberikan peluang bagi UMKM di bidang makanan dan minuman. Kemasan dianggap penting untuk memberikan nilai tambah pada produk, menarik perhatian konsumen, dan meningkatkan potensi pemasaran. Melalui pelatihan pengembangan kemasan dan focus group discussion, Tim PKM Universitas Tarumanagara bertujuan untuk meningkatkan kemampuan UMKM Crème Royale, dalam mengembangkan kemasan yang dapat berdampak positif terhadap pemasaran produk es krim. Kegiatan ini mencakup pelatihan dalam penggunaan aplikasi pembuatan desain, pemilihan bahan, dan manajemen media sosial untuk pemasaran online. Crème Royale telah menggunakan platform Whatsapp dan Instagram untuk pemesanan dan promosi. Pengembangan kemasan diharapkan dapat membantu Crème Royale memasarkan produknya dengan lebih efektif, meningkatkan penjualan, dan berkontribusi pada pertumbuhan ekonomi. Luaran kegiatan yang dihasilkan adalah pengembangan desain kemasan, pengetahuan menyeluruh tentang desain kemasan, dan focus group discussion untuk mengembangkan kemasan yang dapat diimplementasikan oleh Crème Royale. Tim PKM pendaftaran Hak Kekayaan Intelektual untuk desain kemasan es krim Crème Royale. Kegiatan ini dilaksanakan untuk mitra Crème Royale dengan tujuan memberikan bantuan dalam mengembangkan kemasan, meningkatkan potensi pemasaran, dan menyusun dasar rencana kegiatan lanjutan setelah pelaksanaan kegiatan PKM.